CLEAN AND HEALTHY LIFE BEHAVIOR (PHBS) IN NGADIROJO, WONOGIRI REGENCY - Nita Yunianti Ratnasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Clean and Healthy Life Behavior (PHBS) was related to the improvement of individuals, families, society and health environment. Based on the data from the Ministry of Health in 2016, Indonesian households that practiced the PHBS only reached 55.6% and in Central Java reached 75,1 %. The data in Ngadirojo sub-district in 2016 founded that the total number of houses was 14,287 houses, which had beeninspected for 2,244 houses, this data was used as a reference for this research. There are still some villages in Ngadirojo sub-district that have health problems related to PHBS. This study was conducted to know the description of clean and healthy life behavior of the society in the work area of Puskesmas Ngadirojo (KerjoLor and Ngadirojo Kidul Village) Wonogiri Regency, and it was descriptive quantitative research. All the population was heads of household (KK) which were in two research villages of the total 4,556 families. The sample collection used total sampling method, where the number of samples reached1,129 KK in Ngadirojo Kidul and 1,365 KK in Kerjo Lor. The result achievement of PHBS was obtained by KerjoLor village (76,42%) and NgadirojoKidul village (82,75%). From these two villages, there were three PHBS indicators with the lowest value, there were non-smoking (41%), Heath Insurance membership (JPK) (46%), and Family planning program (KB) (52%). The highest PHBS indicators were clean water (99.5%) and healthy latrines (98.5%). PHBS achievement in KerjoLor village (76.42%) was still belowthan the national target, activating health cadres, providing continuous and comprehensive health education to the society and assisting the development of PHBS Keywords: PHBS, Society, Families, PHBS Indicators.